How does ego depletion reduce sports performance in athletes? A systematic meta-analysis - Yan, Xu; Zhong, Jingyi; Wang, Yezheng; Tian, Ying; Wang, Lijuan; Li, Congcong; Liu, Kaihang; Zhao, Wei; Wang, Liyan; Wang, Hongbiao (Frontiers in Psychology, 2025)
PurposeThis meta-analysis focused on exploring whether ego depletion affects sports performance. Subgroup analyses were conducted to compare the magnitude of effect sizes between different ego depletion initiation tasks and which type of sports performance is more susceptible to ego depletion as a moderator variable.MethodsThis article was based on Pubmed, Web of Science, Scopus, EBSCO, Embase, and Cochrane databases for the included articles, and meta-analysis of the included articles was performed using RevMan 5.4 software to evaluate the effect of ego depletion on athletes’ sports performance through standardized mean difference.ResultsEleven articles and 12 studies were finally included. After sensitivity analyses using the Leave-One-Out method, two articles and one experiment were excluded with significant effect sizes. The final total effect size of ego depletion on athletes’ sports performance SMD = −0.38 [95% CI: −0.56 to −0.21], P = 0.001, demonstrating that ego depletion can produce a decrease in athletes’ sports performance. Subgroup meta-analysis showed that the Stroop task SMD = 0.63 [95% CI: −0.96 to −0.26] produced larger effect sizes than the transcription task SMD = 0.39 [95% CI: −0.64 to −0.13], i.e., the Stroop task was more likely to produce ego depletion in athletes. Targeting sports performance SMD = 0.49 [95% CI: −0.74 to −0.23] produced larger effect sizes than endurance-based sports performance SMD = 0.42 [95% CI: −0.68 to −0.16], i.e., aiming-based sports performance was more affected by ego depletion.ConclusionThe total effect size produced by ego depletion on athletes’ sports performance was decreasing, a moderate effect size, and there may be publication bias. The subgroup analyses showed that the amount of effect produced by different ego depletion initiation tasks was different and the Stroop task was more likely to be produced. Also, the effect sizes affected by ego depletion were different for various types of sports performance, with more pronounced for aiming movements.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024561990.